Prevalence of Schistosoma mansoni Infection and Associated Risk Factors among School Children in Jiga Town, Northwest-Ethiopia: A Cross-Sectional Study - Ketemaw Wubet; Destaw Damtie (Journal of Parasitology Research)
Background. Schistosomiasis, one of the 20 Neglected Tropical Diseases, is a human disease which is caused by infection with Schistosoma spp. In Ethiopia, the intestinal form of schistosomiasis (caused by Schistosoma mansoni) is widely distributed. This study is aimed at assessing the prevalence of S. mansoni and associated risk factors among schoolchildren in Jiga town and its surrounding rural “Kebeles”, Northwest Ethiopia (Kebele = the smallest administrative unit in Ethiopia). Methods. A cross-sectional study was carried out among children from three schools in Jiga town and its surrounding rural “Kebeles”. The schools were selected mainly according to their proximity to water bodies that were likely to have been used by the children. A total of 362 randomly selected children were screened for S. mansoni infection. Samples of stool were collected from each pupil and examined by the concentration and microscopic techniques. Semistructured interview questionnaires were administered to the study subjects to identify the possible risk factors of infection with S. mansoni. Data analysis was performed using SPSS version 20 software. Results. The overall prevalence of S. mansoni was 15.2%. A higher proportion of S. mansoni infection (30.3%) was observed at Chifarit primary school children followed by Tikur Wuha primary school children (17.3%) and Jiga 01 primary school children (10.2%). The habit of contact with river water (AOR, 4.86; 95% CI, 0.991-23.8; P=0.051) and the irregular wearing of shoes (AOR, 6.06; 95% CI, 2.61-14.13; P=0.001) were risk factors for S. mansoni infection. Conclusion. S. mansoni infection remains a public health problem in the study area. Snail control, mass deworming, and health promotion are recommended.